History of the Police in Colombia: Assessment and Research Suggestions - Mera, Hansel; Sánchez-Salcedo, José Fernando (Sociedad y Economía, 2022)
The objective of this article is to propose a balance of historiographic studies on the police in Colombia. Its methodological development involves an analytical bibliographical review that contextualizes some global and Latin American references whose results are expressed in the first and second parts, while in the third and fourth parts it proposes a balance of the Colombian case. It is concluded that this is a field of studies in emergence and consolidation for the national case with pending exploration routes, and some research routes are proposed for future approaches focused on the Colombian case.